2017
DOI: 10.1371/journal.pcbi.1005581
|View full text |Cite
|
Sign up to set email alerts
|

A motor unit-based model of muscle fatigue

Abstract: Muscle fatigue is a temporary decline in the force and power capacity of skeletal muscle resulting from muscle activity. Because control of muscle is realized at the level of the motor unit (MU), it seems important to consider the physiological properties of motor units when attempting to understand and predict muscle fatigue. Therefore, we developed a phenomenological model of motor unit fatigue as a tractable means to predict muscle fatigue for a variety of tasks and to illustrate the individual contractile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
119
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 114 publications
5
119
0
1
Order By: Relevance
“…Based on this, we provided (or what we considered to be) a potent resistance exercise prescription to maximize fed‐state myofibrillar protein synthesis rates. Specifically, the volunteers performed resistance exercise at four sets × 10–12 repetitions, with each set performed to volitional failure, which generally serves as a proxy indicator for a strong stimulus being provided to maximize muscle fibre recruitment patterns in both the NW and OB groups (Potvin & Fuglevand, ). Moreover, both the NW and OB groups performed similar amounts of external total work [repetitions × load (kg)] in both absolute terms and when expressed relative to maximal strength (Table ), which resulted in similar blood lactate concentrations immediately after resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we provided (or what we considered to be) a potent resistance exercise prescription to maximize fed‐state myofibrillar protein synthesis rates. Specifically, the volunteers performed resistance exercise at four sets × 10–12 repetitions, with each set performed to volitional failure, which generally serves as a proxy indicator for a strong stimulus being provided to maximize muscle fibre recruitment patterns in both the NW and OB groups (Potvin & Fuglevand, ). Moreover, both the NW and OB groups performed similar amounts of external total work [repetitions × load (kg)] in both absolute terms and when expressed relative to maximal strength (Table ), which resulted in similar blood lactate concentrations immediately after resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Both Steele et al (2018) and Kuznetsov et al (2011) have reported findings suggesting that motor unit recruitment may be similar between modalities and indeed effort has been argued to arise from the central motor command required to drive the musculature to perform the task being attempted (Marcora, 2009;Pageaux et al, 2016). Thus, it is thought that effort, both that required and perceived, is likely intrinsically linked to motor command and motor unit recruitment (de Morree et al, 2012;Guo et al, 2017) and possibly due to Henneman's size principle (Potvin and Fuglevand, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a model was developed by Potvin and Fuglevand (2017a) that predicted that all available MUs would be recruited during low-force isometric contractions to fatigue. These investigators applied this model to compare MU behavior during simulated fatiguing low-(i.e., 20% MVIC) versus high-force contractions (i.e., 80% MVIC), and predicted that low-force contractions sustained to volitional fatigue would result in the eventual recruitment of the entire MU pool (Potvin and Fuglevand 2017b). However, it has been previously shown that, although muscle activation (i.e., EMG amplitude) increases throughout fatiguing submaximal isometric exercise, it may not reach maximal levels (Petrofsky et al 1982;Fuglevand et al 1993).…”
Section: Introductionmentioning
confidence: 99%